Isolation and Characterization of Indigenous Lactic Acid Bacteria from Pakatikng Rape, Dayak’s Traditional Fermented Food - Hanum Mukti Rahayu; Anandita Eka Setiadi (Jurnal Penelitian Pendidikan IPA, 2023)
West Kalimantan is one of the provinces with a variety of traditional foods. One of them is pakatikng rape, a traditional Dayak fermented food made from kelampai fruit. The fermentation process involves lactic acid bacteria which act as food preservatives because they have inhibitory substances known as bacteriocins. Exploration of lactic acid bacteria in the local food fermentation process, especially in West Kalimantan, has not been widely carried out. Therefore, the purpose of this research is to obtain LAB from kelampai fruit fermentation. The research methods included fermentation of kelampai fruit, isolation of LAB, screening for acid-producing LAB, characterization of colony morphology, gram staining, endospore staining, motility test, catalase test, and antibiotic sensitivity test. The results of the study obtained nine isolates that are capable of producing acid and have general characteristics of lactic acid bacteria, namely round cell shape, gram-positive, non-endospores, non-motile and catalase negative and four isolates that are resistant to antibiotics, namely KL-10 resistant to erythromycin, KL-15 and KL-19 resistant to Ofloxacin, and KL-20 resistant to amoxicillin.